COVID-19 autopsies: Procedure, technical aspects and cause of fatal course. Experiences from a single-center - Skok, Kristijan (Pathol Res Pract, 2021)
Autopsies on COVID-19 have provided deep insights into a novel disease with unpredictable and potentially fatal outcome. A standardized autopsy procedure preferably with an in-situ technique and systematic tissue processing is important. Strict safety measures include personal protective equipment with a standardized protocol for dressing and undressing, usage of FFP-3 masks and minimization of aerosol production. The use of an airborne infection isolation (AIIR) room is preferred. Viral RNA analysis using swabs from throat, both lungs and other organs provides information on cross-organ viral dynamics. To correctly determine the full extent of pathological organ changes an adequate processing procedure is of the utmost importance. Systematic dissection and processing of the lungs revealed pulmonary infarction caused by thrombosis and thromboembolism and bacterial bronchopneumonia as the most frequent cause of death. Fungal pneumonia (aspergillus) was found in one case. The quality of the tissue was sufficient for histopathological and immunohistochemistry analyses in all cases. Viral RNA from throat or lung swabs was detectable post mortem in 89 % of the cases and could also be detected from paraffin-embedded tissue by real-time PCR. Complete COVID-19 autopsies including extensive histopathological studies and viral RNA analysis require approximately three times more human and technical resources and time compared to standard non-COVID autopsies. Autopsies on COVID-19 are feasible, present a manageable risk, while following a strict protocol, and provide novel insights into disease pathogenesis and the clinician with important feedback.